TCP factors: new kids on the signaling block. (October 2016) - Nicolas, Michael; Cubas, Pilar
Highlights: TCP factors play important roles in the modulation of phytohormone signaling. TCPs are involved in the synthesis of jasmonate, brassinosteroids, salicylic acid and auxin. TCPs interact with DELLA proteins and mediate some GA responses. Class I and II TCPs play antagonistic or additive functions in hormone signaling. Some TCPs-hormone genetic modules are conserved throughout angiosperms. Abstract : The TCP transcription factors govern key plant developmental processes and have profound effects on the growth patterns of meristems and organs, partly explained by direct transcriptional control of cell cycle genes. This view is nevertheless incomplete, as accumulated evidence indicates that TCPs also act through other mechanisms, such as the regulation of hormone activity. Several TCP factors not only act as mediators of hormone-induced changes in cell proliferation, but also as modulators, or even key players, of hormone synthesis, transport and signal transduction. This adds another layer of complexity to the role of TCPs in plant development.